EXPERIMENTAL ANALYSIS OF HYDRODYNAMIC SIMPLE JOURNAL BEARING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The new machine design applications require high operating speed, higher power density, small size, high load carrying capacity and to full fill this requirement it is necessary to consider transmission section. So one of the most important element to be considered for design is bearing. Bearing not only support rotor weight and operating speed but also influence on rotor dynamic behaviour This constant trend towards higher power densities in rotating machinery calls for better mechanical components capable of carrying higher loads while being the same or smaller in size without sacrificing machine safety. For hydrodynamic bearings it is important that minimum film thickness never drops below a safety limit. An oil film becomes thinner if load increases. This also results in elevated temperatures, which reduce oil viscosity and further decrease oil film thickness. When the fluid-film bearings operate under high speed, heat is generated within the oil film due to shearing of the lubricant and temperature rise of the lubricant fluid film and the bearing surface takes place